An Innate Preference of Bumblebees for Volatile Organic Compounds Emitted by Phaseolus vulgaris Plants Infected With Three Different Viruses - Mhlanga, Netsai Margareth; Murphy, Alex M.; Wamonje, Francis O.; Cunniffe, Nik J.; Caulfield, John C.; Glover, Beverley J.; Carr, John P. (Frontiers in Ecology and Evolution, 2021)
Cucumber mosaic virus (CMV)-infected tomato (Solanum lycopersicum L.) plants emit volatile organic compounds (VOCs) attracting bumblebees (Bombus terrestris L.), which are important tomato pollinators, but which do not transmit CMV. We investigated if this effect was unique to the tomato-CMV pathosystem. In two bean (Phaseolus vulgaris L.) cultivars, infection with the potyviruses bean common mosaic virus (BCMV) or bean common mosaic necrosis virus (BCMNV), or with the cucumovirus CMV induced quantitative changes in VOC emission detectable by coupled gas chromatography–mass spectrometry. In free-choice olfactometry assays bumblebees showed an innate preference for VOC blends emitted by virus-infected non-flowering bean plants and flowering CMV-infected bean plants, over VOCs emitted by non-infected plants. Bumblebees also preferred VOCs of flowering BCMV-infected beans of the Wairimu cultivar over non-infected plants, but the preference was not significant for BCMV-infected plants of the Dubbele witte cultivar. Bumblebees did not show a a significant preference for VOCs from BCMNV-infected flowering bean plants but differential conditioning olfactometric assays showed that bumblebees do perceive differences between VOC blends emitted by flowering BCMNV-infected plants over non-infected plants. These results are consistent with the concept that increased pollinator attraction may be a virus-to-host payback, and show that virus-induced changes in bee-attracting VOC emission is not unique to one virus-host combination.